Indigenous medicinal plants of the Kani tribes in Kanyakumari District: Ethnobotanical documentation and quantitative study - Palanisamy Prakash; Gopi Mohanakrishnan
The investigation identified 120 species distributed in 54 families. 70 plants of ethnomedicinal importance were identified, which have not yet been reported so far from the Kanyakumari wildlife forest of Southern-Western Ghats. 52participants were approached three times to verify the information provided by twenty informants. This approach was undertaken to ensure the accuracy and reliability of the data collected. The data quality was ensured by selecting well-trained 20 practitioners for pointing out missing information if any and the data is carefully analyzed. In total, 120 Medicinal plant species of which Dicot plants constitute 116 species (96.7%) and monocot plant constitutes 4 species (3.3%). Fabaceae with 12 (10.00%) was the most commonly reported family of medicinal plant species. The habit-wise study revealed that 40 species (33.33%) were trees, followed by the most widely used life types herb (36 species) (30%). The most popular preparation method for treating the ailment was paste (40 preparations) for internal consumption as well as external application. The documents valuable therapeutic knowledge, which opens up possibilities for future exploration in plant-based compounds and pharmaceutical inquiry. These investigations have the potential to contribute to the development of plant-based nanomedicine, drug discovery, and production. Finally, the paper deals with the combination of socio-economic and legal facets of the interaction between tribals and forests.